2016
DOI: 10.1111/apha.12825
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous exposure to hypoxia does not affect skin perfusion in humans

Abstract: Reductions in skin-surface PO do not affect skin perfusion in humans. The unchanged epidermal HIF-1α expression suggests that epidermal O homoeostasis was not disturbed by Hypoxia /Anoxia , potentially due to compensatory increases in arterial O extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Recently, a small study in nine males showed hypoxia increasing epidermal hypoxia inducible factor-1α (HIF-1α) followed by nitrous oxide-mediated vasodilatation in skin. However, cutaneous hypoxia alone does not affect microcirculation (Siebenmann et al, 2017 ). Another small study in 11 subjects observed an increase in forearm skin blood flow after systemic hypoxia, without impact of local regulatory factors (Paparde et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a small study in nine males showed hypoxia increasing epidermal hypoxia inducible factor-1α (HIF-1α) followed by nitrous oxide-mediated vasodilatation in skin. However, cutaneous hypoxia alone does not affect microcirculation (Siebenmann et al, 2017 ). Another small study in 11 subjects observed an increase in forearm skin blood flow after systemic hypoxia, without impact of local regulatory factors (Paparde et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Siebenmann et al reported that cutaneous exposure to hypoxia has no effect on skin perfusion in humans (Siebenmann et al, 2017). A meta-analysis shows that athletes present enhanced microvascular function compared with untrained but otherwise healthy subjects (Montero et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue of how a hypoxic stimulus influences microcirculation and microcirculatory blood flow is still debating and under investigation (Simmons et al, 2007;Siebenmann et al, 2017;Treml et al, 2018). Paparde et al found that acute systemic hypoxia causes sympathetic stimulation to the heart, which results in an increased heart rate and enlarged cardiac output, and that may lead to increment in forearm skin blood flow increment during acute systemic hypoxia (Paparde et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent hypoxia training had greater positive effect on hemodynamics, microvascular endothelial function, and work capacity of untrained healthy men (Shatilo et al 2008). However, the issue of how a hypoxia stimulus influences the microcirculation and microcirculatory blood flow is still debating and under investigated (Rowell et al 1982, Simmons et al 2007, Siebenmann et al 2017, Treml et al 2018. Paparde et al (2015) found that acute systemic hypoxia causes sympathetic stimulation to heart which results in increased heart rate and larger cardiac output, and which could be the reason of forearm skin blood flow increase in acute systemic hypoxia.…”
Section: Introductionmentioning
confidence: 99%